Effect of Extrusion and Konjac Flour Addition on the Antioxidant Activity, Structural Properties, and In vitro Digestibility of Extruded Oat–Corn Flour. (25th January 2022) - Huo, Rui; Zhang, Meili; Guo, Xinyue; Zhang, Yakun; Zhang, Yuanyuan; Bai, Xue; Zhang, Jing
Abstract: Oat–corn extruded powder is prepared to explore the effect of co‐extrusion with konjac flour on the structural properties and functional properties of the mixed powder for a reduced starch digestion rate. Scanning electron microscopy (SEM), X‐ray diffraction (XRD), Fourier transform infrared spectroscopy (FT‐IR), antioxidant activity, and in vitro digestibility are applied for analysis. SEM images after extrusion treatment show irregularity of the surface with some cracks and grooves. XRD and FT‐IR results show that the A‐type crystal structure disappears after extrusion, and the in vitro digestibility is improved but not significantly ( p > 0.05). After different amounts of konjac flour and oat and corn mixed powder are added for co‐extrusion, the surface microstructure is relatively rough, the pores of the mixed system are reduced, the crystal form is V‐shaped. The starch digestion rate is significantly decreased ( p < 0.05). The mixed powder with the addition of 5–15% konjac flour is a low GI material. It can be used as a raw material for meal replacement products. Abstract : Mixed grain flour is prepared and the antioxidant properties, structural properties, and in vitro digestibility of starches co‐extruded with konjac flour are analyzed. The product has the characteristics of slow digestion, and the process is simple and there is no chemical residue.